School Branding as a Driver of Institutional Competitiveness: Insights from a Qualitative Case Study in Indonesia - Galih Permadi; Moh. Khusnuridlo; Ainur Rafik; Achmad Mahrus Helmi (Universitas Nurul Jadid, 2025)
This study examines the implementation of school branding strategies in developing institutional image and enhancing the attractiveness of prospective students at MAN Lumajang. The research addresses the increasing competition among educational institutions, which requires schools to establish strong identities and gain public trust. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and document analysis involving key stakeholders, including the principal, vice principals, students, and parents. The findings reveal that MAN Lumajang implements a holistic and integrated branding strategy that combines academic excellence, skill-based programs, and Islamic character development. Branding is not only carried out through external promotion but also through strengthening internal quality and institutional culture. The use of multi-channel communication, including social media and collaboration with stakeholders, plays a significant role in disseminating the institution’s achievements and values. The results indicate that this strategy has successfully transformed public perception, strengthened institutional credibility, and increased student enrollment. The study highlights that effective school branding requires alignment between institutional values, practices, and communication strategies. These findings provide practical insights for educational institutions in developing sustainable branding strategies to enhance competitiveness and public trust.